I believed the answer is 16 but computer teacher is telling me it 1. Thanks
when x = 17
f(17) = f(14) + 2
f(14) = f(11) + 2
f(11) =f (8) + 2
but f(8) = -5 , since x ≤ 10
so f(11) = -5+2 = -3
f(14) = -3+2 = -1
f(17) = -1+2 = +1
Let say the other function is
x-2 , if x < 0
x^2 + 1 , if x >= 0
f(-4) would be -6? I kind of not understand why do we keep going down the value. Thanks
In this last example your function is well defined as
f(x) = x-2 or x<0 and f(x) = x^2 + 1 for x≥0
so f(-4) simply falls in the first part
f(x) = x-2
f(-4) = -4 - 2 = -6 , so you are right.
Your first problem did not have f(x) defined explicitly.
It was defined in terms of f(x-3)
so we had to find values step-by-step
Oh, thanks you so much! I did not realize f(x-3) and (x-3) make such different.
Answer this Question
PreCalculus - Write an equation to construct a function whose graph is like ...
College Algebra - Give a piece-wise function p(x) where p(2)=5 and p(-1)=3
Piecewise function - write a piece-wise function over 3 intervals whose domain ...
calculus - A 12,000 liter tank filled to capacity at t=0 drains at rate r(t), ...
Math - i am trying to transform a piece wise function, but my problem is that ...
Chemistry - Choose the bond that is the weakest: A) Na-Cl B) I-I C) C=N D) Li-F ...
English - It is very rude of you to behave like that. It is very wise of you to ...
pre cal - you decide to buy a car for 25000. each year your car depreciates in ...
Math - Would someone please check my answers to this problem: The license fee ...
Algebra! - 4. A ball is thrown into the air with an initial upward velocity of ...